Trichoderma Applications on Strawberry Plants Modulate the Physiological Processes Positively Affecting Fruit Production and Quality - Lombardi, Nadia; Caira, Simonetta; Troise, Antonio Dario; Scaloni, Andrea; Vitaglione, Paola; Vinale, Francesco; Marra, Roberta; Salzano, Anna Maria; Lorito, Matteo; Woo, Sheridan Lois (Frontiers in Microbiology, 2020)
Many Trichoderma spp. are successful plant beneficial microbial inoculants due to their ability to act as biocontrol agents with direct antagonistic activities to phytopathogens, and as biostimulants capable of promoting plant growth. This work investigates the effects of treatments with three selected Trichoderma (strains T22, TH1 and GV41) to strawberry plants on the productivity, metabolites and proteome of the formed fruits. The Trichoderma applications stimulated plant growth, increased strawberry fruit yield, and favored selective accumulation of anthocyanins and other antioxidants in red ripened fruits. Proteomic analysis of fruits harvested from the plants previously treated with Trichoderma demonstrated that the microbial inoculants highly affected the representation of proteins associated with responses to stress/external stimuli, nutrient uptake, protein metabolism, carbon/energy metabolism and secondary metabolism, also providing a possible explanation to the presence of specific metabolites in fruits. Bioinformatic analysis of these differential proteins revealed a central network of interacting molecular species, providing a rationale to the concomitant modulation of different plant physiological processes following the microbial inoculation. These findings indicated that the application of Trichoderma-based products exert a positive impact on strawberry, integrating well with previous observations on the molecular mechanisms activated in roots and leaves of other tested plant species, demonstrating that the efficacy of using a biological approach with beneficial microbes on the maturing plant is also able to transfer advantages to the developing fruits.